2001
DOI: 10.1021/bi010207k
|View full text |Cite
|
Sign up to set email alerts
|

FK506 Blocks Intracellular Ca2+ Oscillations in Bovine Adrenal Glomerulosa Cells

Abstract: The inositol 1,4,5-trisphosphate (InsP(3)) receptor is a ligand-gated Ca(2+) channel playing an important role in the control of intracellular Ca(2+). In the study presented here, we demonstrate that angiotensin (AngII), phorbol ester (PMA), and FK506 significantly increase the level of InsP(3) receptor phosphorylation in intact bovine adrenal glomerulosa cells. With a back-phosphorylation approach, we showed that the InsP(3) receptor is a good substrate for protein kinase C (PKC) and that FK506 increases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…In nuclei isolated from rat liver (unknown composition of IP 3 R/channel), PKC enhanced IP 3 -induced Ca 2C release (Matter et al 1993). In bovine adrenal glomerulosa cells, which express all three subtypes of IP 3 R (but a large majority of IP 3 R-1), PKC enhanced IP 3 -induced Ca 2C release (Poirier et al 2001). In rat brain microsomes, a tissue containing exclusively the IP 3 R-1 subtype, PKC also increased IP 3 -induced Ca 2C release (Cameron et al 1995).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In nuclei isolated from rat liver (unknown composition of IP 3 R/channel), PKC enhanced IP 3 -induced Ca 2C release (Matter et al 1993). In bovine adrenal glomerulosa cells, which express all three subtypes of IP 3 R (but a large majority of IP 3 R-1), PKC enhanced IP 3 -induced Ca 2C release (Poirier et al 2001). In rat brain microsomes, a tissue containing exclusively the IP 3 R-1 subtype, PKC also increased IP 3 -induced Ca 2C release (Cameron et al 1995).…”
Section: Discussionmentioning
confidence: 96%
“…We also demonstrated that endogenous PKC phosphorylates IP 3 R-2 in intact AR4-2J cells. Previous studies demonstrated that IP 3 Rs are a substrate for PKC but these studies were done with cells or tissues expressing exclusively the IP 3 R-1 subtype (Cameron et al 1995), or a mixture of all three IP 3 R subtypes (Matter et al 1993, Poirier et al 2001. A recent study reported that full-length mouse IP 3 R-1 and full-length rat IP 3 R-3 expressed in Sf9 insect cells are good substrates for PKC (Vermassen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been described that mTOR may stimulate phosphorylation of 4E-BP1 indirectly by inactivating some phosphatases (PP2A, PP4, PP6) that would lead to the phosphorylation of 4E-BP1 (47), but it is not known how PP2A or these other phosphatases are regulated. It has also been described that 4E-BP1 phosphorylation can be dependent on calcium and calmodulin activation, independently of the PI3K/Akt/mTOR pathway activation (47) (43). However, the lack of a strong effect on amylase secretion makes this mechanism unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…This association increases IP 3 R phosphorylation and enhances Ca 2+ release (Cameron et al, 1995a). Again, in adrenal glomerulosa cells, both Ca 2+ signalling and protein kinase C (PKC)-mediated phosphorylation of the IP 3 R were modified by FK506 (Poirier et al, 2001), whereas in COS-7 cells, calcineurin reduced IP 3 -induced Ca 2+ release, an effect reversed by FK506 (Bandyopadhyay et al, 2000). However, as with FKBP12, the mechanisms by which calcineurin regulates Ca 2+ release from IP 3 R are disputed.…”
mentioning
confidence: 99%